Effect of Aloe vera and Curcuma longa (Turmeric) on Carcass Characteristics and Biochemical Parameters of Broilers - Mehala, C.; Moorthy, M. (International Journal of Poultry Science, 2008)
An experiment was conducted to study the inclusion of Aloe vera and Curcuma longa and its combinations on production performance, viz., weight gain, feed intake and feed conversion ratio, carcass characteristics and biochemical parameters for a period of six weeks with two hundred and eighty commercial, straight run day-old Vencobb broiler chicks. These chicks were randomly grouped into seven treatments with four replicates of ten chicks each. The treatment groups consisted of control (T1), 0.1 percent Aloe vera powder (T2), 0.2 percent Aloe vera powder (T3), 0.1 percent Curcuma longa powder (T4), 0.2 percent Curcuma longa powder (T5) and 0.1 percent of Aloe vera and 0.1 percent of Curcuma longa powder (T6) and 0.2 percent of Aloe vera and 0.2 percent of Curcuma longa powder (T7) included in the broiler diet. The abdominal fat percentage, breast and thigh muscle cholesterol showed no significant difference between treatment groups. The serum glucose, total cholesterol, HDL cholesterol, LDL cholesterol and triglycerides level did not differ significantly between treatment groups. Haemagglutination inhibition titre against Newcastle disease revealed significant difference (P < 0.01) between treatment groups. T2 and T3 showed higher titre value when compared with control.